1955
DOI: 10.1071/ar9550640
|View full text |Cite
|
Sign up to set email alerts
|

The function of cattle sweat glands.

Abstract: Evidence is presented that the apocrine sweat glands of cattle have a temperature-regulating function. Under the stereo microscope, sweat droplets could be observed forming at the openings of the sweat gland ducts in response to intradermal injections of adrenaline, and during exposure to hot conditions. The sweat spots could be stained macroscopically, and prints showing the location of the spots were obtained with bromothymol blue papers pressed onto the skin surface. Quantitative measurements indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 1 publication
3
29
0
Order By: Relevance
“…It is possible to determine the air-flow rate at which AT = 0; this 'critical flow rate' gives ventilation inside the capsule equivalent to that outside it. The critical flow rate determined at this air temperature may be still valid at other air temperatures; but the condition AT = 0 is no longer applicable, & Robinson, 1955;e Taneja, 1958;f Kibler & Yeck, 1959;g McDowell, Lee & Fohrman, 1954;h, McDowell, McDaniel, Barrada & Lee, 1961;j, Taneja, 1959;k, Ferguson & Dowling, 1955. 27-2 420 J. A. McLEAN since radiative loss is now altered by the application of the capsule.…”
mentioning
confidence: 99%
“…It is possible to determine the air-flow rate at which AT = 0; this 'critical flow rate' gives ventilation inside the capsule equivalent to that outside it. The critical flow rate determined at this air temperature may be still valid at other air temperatures; but the condition AT = 0 is no longer applicable, & Robinson, 1955;e Taneja, 1958;f Kibler & Yeck, 1959;g McDowell, Lee & Fohrman, 1954;h, McDowell, McDaniel, Barrada & Lee, 1961;j, Taneja, 1959;k, Ferguson & Dowling, 1955. 27-2 420 J. A. McLEAN since radiative loss is now altered by the application of the capsule.…”
mentioning
confidence: 99%
“…The increased rate of loss of moisture from the skin after the injection of adrenaline must therefore have been due to the active expulsion of moisture from sweat glands or sebaceous glands in the thorax and shanks. The active secretion of sweat from the skin of cattle has been observed before by Ferguson & Dowling (1955), who examined the orifices of the sweat glands under a stereo microscope during intradermal injections of adrenaline. Evans & Smith (1956) have demonstrated that the sweat glands in the horse normally respond to an increase in the amount of adrenaline in the blood or to increased blood supply, and that factors which increase skin circulation therefore favour or cause sweating.…”
Section: The Effects Of Localized Infra-red Irradiationmentioning
confidence: 99%
“…The relationship between sweating rate and rectal temperature was greater for Brahman cattle (B) than for the Brahman cross Shorthorn (BX) or Shorthorn cattle (S). The density of sweat glands in Bos indicus is higher than in European cattle (Ferguson & Dowling 1955;Nay and Hayman 1956). Nay and Hayman (1956) found that Bos indicus cattle had larger and more numerous sweat glands than Bos taurus cattle.…”
Section: The Effects Of Heat Load On Different Breeds Of Cattle (Bos mentioning
confidence: 99%
“…Others have shown that a sweating mechanism is in fact present (Dowling 1955a(Dowling , 1955bFerguson & Dowling 1955;Taneja 1956;Dowling 1958). …”
Section: Sweatingmentioning
confidence: 99%